2003
DOI: 10.1038/sj.ejcn.1601588
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a semi-quantitative adolescent food frequency questionnaire applied at a public school in São Paulo, Brazil

Abstract: Objective: To develop a food frequency questionnaire for adolescents (AFFQ) and demonstrate its relative validity. Design: The final version of the AFFQ was composed of 76 food items previously identified according to their contribution in nutrients and overall importance within the eating habits of this population group. The validation study, which was undertaken during a 6 month period (June to November 1999), was administered to a sample of 79 who answered at least three 24 h dietary recalls (R24 h) applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

20
145
3
46

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(214 citation statements)
references
References 26 publications
20
145
3
46
Order By: Relevance
“…Also in comparison with their results, our study found similar energy-adjusted correlation coefficients for macronutrients. With the exception of results by Slater et al (14) , which showed higher correlations for energy (0?86 for females), the correlations were not very high (Table 5). Divergence for sweets/snacks was shown in the present study, with an estimated intake of 664 kJ while the actual intake was 100 kJ for sweets/snacks, which were included in a list of confectioneries and beverages, and the median of the difference was 381 kJ.…”
Section: Validity and Reliabilitymentioning
confidence: 60%
See 2 more Smart Citations
“…Also in comparison with their results, our study found similar energy-adjusted correlation coefficients for macronutrients. With the exception of results by Slater et al (14) , which showed higher correlations for energy (0?86 for females), the correlations were not very high (Table 5). Divergence for sweets/snacks was shown in the present study, with an estimated intake of 664 kJ while the actual intake was 100 kJ for sweets/snacks, which were included in a list of confectioneries and beverages, and the median of the difference was 381 kJ.…”
Section: Validity and Reliabilitymentioning
confidence: 60%
“…The accurate assessment of nutritional intake is important in epidemiological studies. Although under-reporting of energy intake in young people has been shown (7) , the FFQ is feasible for this purpose (8) , considering the circumstances of young people that prohibit them from weighing foods, such as school attendance, as well as their ability to meticulously record food intake.Thus far, various FFQ have been assessed to determine their validity for use in young people in Western countries (9)(10)(11)(12)(13)(14)(15)(16) . To our knowledge, however, no study has determined the effectiveness of an FFQ in acquiring information on the diets of young people in Japan.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Results generally show a strong agreement in test-retest for foods (3) and nutrients (4)(5)(6)8) , but often a high variability in the dietary intake of adolescents (5,9) .…”
mentioning
confidence: 93%
“…A limited number of validation studies of FFQ for adolescents have been conducted internationally (3)(4)(5)(6)(7)(8) , with a minority in developing countries (9) . Results generally show a strong agreement in test-retest for foods (3) and nutrients (4)(5)(6)8) , but often a high variability in the dietary intake of adolescents (5,9) .…”
mentioning
confidence: 99%